A 2-D Analytical Threshold Voltage Model for Symmetric Double Gate MOSFET's Using Green’s Function - Anoop Garg; S.N. Sinha; R.P. Agarwal (Журнал нано- та електронної фізики)
We propose a new two dimensional (2D) analytical solution of Threshold Voltage for undoped (or lightly doped) Double Gate MOSFETs. We have used Green’s function technique to solve the 2D Poisson equation, and derived the threshold voltage model using minimum surface potential concept. This model is assumed uniform doping profile in Si region. The proposed model compared with existing literature and experimental data and we obtain excellent agreements with previous techniques.